Potret Pola Pendidikan Agama Islam Keluarga Pekerja Perkebunan Teh Desa Tangsi Baru Kabawetan - Leni Marlina; Fakruddin Fakruddin; Muksal Mina Putra (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: The Portrayal Of Islamic Religious Education Patterns Of The Workers’ Family At The Tea Plantation In Tangsi Baru Village KabawetanThe family is a small part of society that consists of father, mother (parents), and children. Parents are the first and foremost educators for every child. When parents have other professions outside the home, they definitely still have to prioritize religious education for their children even since early years. In this regard, how are the patterns of familial education in Tangsi Baru Village, Kabawetan, Kepahiang Regency, in the midst of families as the tea laborers? To answer the foregoing question, this study used a qualitative approach. The data collection techniques were interviews and observations, and the data were then analyzed in a qualitative way. The conclusion is showed that the most widely applied pattern of Islamic education in the family was a democratic pattern, with the reason in order that their children are not circumscribed by the parents’ rules, in the meantime their control is very limited because of being the plantation workers